2019
DOI: 10.3400/avd.oa.19-00011
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Surgical Treatment of Symptomatic Primary Varicose Veins Decreases Systemic Inflammatory Biomarkers

Abstract: Objective: To evaluate the relationship between systemic inflammatory biomarkers and efficacy of surgical treatment of primary varicose veins of the lower extremities.Methods: Total 12 patients who underwent endovenous laser ablation or stripping of varicose veins and six healthy subjects were enrolled. Structural and molecular changes of varices were assessed by immunohistochemical staining with anti-monocyte chemotactic protein-1 (MCP-1). MCP-1 and interleukin-6 (IL-6) levels in systemic antecubital blood we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(11 reference statements)
0
2
0
1
Order By: Relevance
“…Sci. 2023, 24,1928 9 of 14 also some clinical studies that confirmed MCP-1 serum concentration changes after venous invasive procedures and also after venoactive drug treatment, and this may account for its role as an effective biomarker in CVD clinical management [107][108][109][110]. Figure 1 summarizes the main pathophysiological steps in CVD development that have been discussed so far in various sections of this article.…”
Section: The Role Of Endothelial Dysfunction In Cvdmentioning
confidence: 87%
See 1 more Smart Citation
“…Sci. 2023, 24,1928 9 of 14 also some clinical studies that confirmed MCP-1 serum concentration changes after venous invasive procedures and also after venoactive drug treatment, and this may account for its role as an effective biomarker in CVD clinical management [107][108][109][110]. Figure 1 summarizes the main pathophysiological steps in CVD development that have been discussed so far in various sections of this article.…”
Section: The Role Of Endothelial Dysfunction In Cvdmentioning
confidence: 87%
“…In this regard, a study showed a preventive effect on varicose vein development after MCP-1 expression suppression [106]. Moreover, there are also some clinical studies that confirmed MCP-1 serum concentration changes after venous invasive procedures and also after venoactive drug treatment, and this may account for its role as an effective biomarker in CVD clinical management [107][108][109][110].…”
Section: The Role Of Endothelial Dysfunction In Cvdmentioning
confidence: 91%
“…No nosso estudo, curiosamente, evidenciamos uma diminuição do TAT tanto no pós-operatório dos casos de SFN quanto no de RFA em 30 dias. Alguns estudos relacionam a presença de varizes com estados inflamatórios ou pró-trombóticos elevados e, quando é feito o tratamento cirúrgico, ocorre uma diminuição desses fatores (ARASE, et al, 2019). Esta poderia ser, uma explicação deste comportamento inesperado do TAT.…”
Section: -Discussãounclassified